Cytoskeletal and contractile proteins modulate microvascular cell function. - Durham, Jennifer. (2017)
Abstract: Endothelial cell migration and proliferation, central steps in both physiologic and pathologic angiogenesis, require cytoskeletal-dependent remodeling, which is achieved by the dynamic regulation of the β-actin network. Specifically, the β-actin network has previously been shown to be enriched in regions of motile cytoplasm, and modulated by its isoactin-specific barbed-end capping protein, βcap73. We hypothesize that regulated over-expression of βcap73 could disrupt angiogenesis by capping β-actin-filament assembly, thus inhibiting the incipient cellular migration and microvascular morphogenesis. Indeed, upon infection of capillary endothelial cells (cEC) with an adenovirus encoding the full-length βcap73 (Ad-βcap73), there is a robust cellular rounding response that occurs concomitantly with cytoskeletal disruption. Further, we demonstrate that over-expression of Ad-βcap73 inhibits cEC migration in wound healing studies. Quantitative in vitro angiogenesis assays reveal that Ad-βcap73 prevents endothelial cells from forming capillary-like networks, and also induces the collapse of preformed endothelial tubes. In testing whether βcap73 impairs angiogenic events by inducing anoikis/apoptosis, we demonstrate that Ad-βcap73 infection activates a caspase-3-mediated cell death response as observed by quantitative Western blotting and immunofluorescence analyses. To confirm and extend these findings in vivo, we have engineered a 'two-mouse' transgenic approach, to specifically induce βcap73 over-expression within the post-natal vascular endothelium using a hypoxia-induced model of retinopathy of prematurity. Indeed, βcap73 over-expression reduces the pathologic angiogenic response by approximately 30%. This work demonstrates that endothelial cell-specific targeting of actin-mediated assembly processes may be used as a novel therapeutic approach to eradicate unwanted angiogenesis accompanying disease. Vascular tone regulates blood pressure and tissue perfusion, and is modulated by vascular smooth muscle cells and pericytes. Phosphorylation of the myosin light chain, which is controlled by opposing actions of myosin light chain phosphatase (MLCP) and myosin light chain kinase (MLCK), modulates mural cell contractile phenotype. While the RhoA/Rho Kinase (ROCK) pathway has been shown to control pericyte contractile phenotype, the mechanisms linking RhoGTPase activity and the cytoskeleton remain incompletely understood. Recently, the myosin phosphatase-RhoA interacting protein (MRIP) has been described to mediate the RhoA/ROCK-directed inactivation of MLCP, by localizing RhoA and MLCP to stress fibers. Here, we report a novel interaction between MRIP and the β-actin specific capping protein, βcap73. Dramatic alterations in cytoskeletal architecture accompany increased pericyte contractility upon MRIP knockdown. Ultimately, these MRIP-silenced, hyper-contractile pericytes are unable to maintain contact-mediated endothelial cell growth arrest. This newly characterized interaction between MRIP and βcap73 should offer insights into the actomyosin dynamics controlling pericyte contractility, and inappropriate regulation of this complex might have implications during microvascular pathologies, including essential hypertension and proliferative diabetic retinopathy.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Cellular & Molecular Physiology.; Advisors: Ira Herman, and Brent Cochran.; Committee: Laura Liscum, Howard Surks, and Michael Gimbrone.; Keywords: Physiology, and Biology.